2021
DOI: 10.1007/s11056-021-09881-y
|View full text |Cite
|
Sign up to set email alerts
|

Less is more: Little seed processing required for direct seeding in seasonal tropics

Abstract: Seed processing and dormancy break treatments are recommended for rendering seeds restoration-ready. Conversely, fruit structures and seed coats may protect seeds from environmental harm in the field. We evaluated the effects of seed processing (by either keeping fruit structures or extracting seeds) and/or scarification (of physically dormant seeds) on the seedling emergence and establishment of 10 legume tree species from tropical forests and savannas of Central Brazil. We sowed seeds in a greenhouse for ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The survival of species planted via DS was relatively high when compared with SP. Other studies conducted in the seasonal tropics have shown high survival rates of DS (Pellizzaro et al 2017; Silva & Vieira 2017; Correia et al 2022) as well as of SP (Navarro‐Cerrillo et al 2011; Scaloppi & de Souza 2020). The lower survival in SP of As.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The survival of species planted via DS was relatively high when compared with SP. Other studies conducted in the seasonal tropics have shown high survival rates of DS (Pellizzaro et al 2017; Silva & Vieira 2017; Correia et al 2022) as well as of SP (Navarro‐Cerrillo et al 2011; Scaloppi & de Souza 2020). The lower survival in SP of As.…”
Section: Discussionmentioning
confidence: 93%
“…Mortality was very low in the DS (7%) when compared to other studies conducted in the seasonal tropics (33% in Silva & Vieira 2017; 23% in Pellizzaro et al 2017; 55% in Souza & Engel 2018). This high survival rate can be explained by the careful measures taken for seeding (Shaw et al 2020; Correia et al 2022), and by managing the invasive plant incidence since the start of the experiment. Overall DS survival rate was 29% higher in plots where exotic grasses were eliminated, when compared to control, for 10 species of savanna (Passaretti et al 2020), and 44% higher for 7 species (Pereira et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Larger seeds typically have more stored energy and water, which can lead to higher germination rates and faster emergence (Baskin & Baskin, 2014). Seeds with low moisture content and those with protective coats are more likely to germinate successfully due to their ability to avoid dehydration in hot and dry seeding sites (Correia et al., 2022; Dias Laumann et al., 2023). Thick seed coats can protect seeds from harsh environmental conditions but can also impede water uptake and gas exchange, potentially delaying or preventing germination (Bewley & Black, 2013).…”
Section: Introductionmentioning
confidence: 99%